2021
DOI: 10.3390/antibiotics10091061
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Multidrug-Resistant Helicobacter pylori in Southeast Asia: A Systematic Review on the Trends and Intervention Strategies Using Antimicrobial Peptides

Abstract: The emergence of multidrug-resistant H. pylori poses a public healthcare threat, particularly in low- and middle-income countries. Recently, the World Health Organization has classified clarithromycin-resistant H. pylori as high priority in the research and discovery of novel antibiotics. This study was aimed to systematically review the prevalence of primary antibiotic resistance in H. pylori in Southeast Asian countries (SEAC) and to review current studies of antimicrobial peptides against H. pylori. We syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
(108 reference statements)
4
32
0
Order By: Relevance
“…Differences in the cost of treatment were only evaluated by Al‐Eidan et al 18 It was reported that treatment accompanied by TEC would cost £8402 per hundred patients, saving an estimated £3026 over those who underwent the same eradication regime with traditional clinic visits. They suggest that this is attributed to the better eradication rates for patients undergoing TEC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the cost of treatment were only evaluated by Al‐Eidan et al 18 It was reported that treatment accompanied by TEC would cost £8402 per hundred patients, saving an estimated £3026 over those who underwent the same eradication regime with traditional clinic visits. They suggest that this is attributed to the better eradication rates for patients undergoing TEC.…”
Section: Resultsmentioning
confidence: 99%
“…6 This is further compounded by the rising trend of resistance, partly from poor compliance, which can undermine the efficacy of treatment regimes. 18 Large-scale studies have demonstrated the effectiveness of TEC modalities in improving treatment outcomes in various other clinical scenarios. 19 However, its…”
Section: Follow-up Ratesmentioning
confidence: 99%
“…In conclusion, our report confirmed that BQT is effective as an empiric second-line regimen. Therefore, its use may be recommended, but it should be adopted with caution since inappropriate use could undermine its effectiveness, taking into account the risk of tetracycline resistance spreading [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality and incidence of gastric cancer were high in the Republic of Korea and Japan, but continuous effort for early screening and eradication of H. pylori infection has contributed to the decline of the cancer in these countries in recent years [ 18 ]. Nevertheless, the rise of antibiotic resistance of H. pylori to essential antibiotics for treatment purposes that has been observed in recent years has complicated the prevention strategy of gastric cancer, particularly in developing countries [ 19 ]. In China, the prevalence of gastric cancer is showing an overall downward trend among patients aged more than 50 years old.…”
Section: Prevalence and Incidence Of Gastric Cancer Worldwidementioning
confidence: 99%